2003
DOI: 10.1007/bf03179887
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microcystin-LR on the activity of membrane enzymes in rat intestinal mucosa

Abstract: I. M. MORENO, A. MATE, G. REPETTO, C. M. VÁZQUEZ and A. M. CAMEÁN. Influence of Microcystin-LR on the activity of membrane enzymes in ratintestinal mucosa. J. Physiol. Biochem., 59 (4), [293][294][295][296][297][298][299][300] 2003.The objective of the present study was to evaluate the effects of microcystin-LR (MCLR) on the activity of membrane enzymes from intestinal mucosa. In addition, serum chemistry and peroxidative status of both serum and intestinal homogenate were evaluated after treatment with MCLR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 21 publications
3
36
0
Order By: Relevance
“…Liver has been described as the most important organ involved in the regulation of redox metabolism (Klaassen, 2001), due to synthesis of key enzymes responsible for reactive oxygen species clearance and production of the most important systemic antioxidant agent, glutathione (GSH). On the other hand, it has been proven that MC-LR promotes renal and intestinal alterations and affects renal physiology (Nobre et al, 2003;Moreno et al, 2003). Thus, it could be assumed that MCs affected the functions of the detoxification system of these organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver has been described as the most important organ involved in the regulation of redox metabolism (Klaassen, 2001), due to synthesis of key enzymes responsible for reactive oxygen species clearance and production of the most important systemic antioxidant agent, glutathione (GSH). On the other hand, it has been proven that MC-LR promotes renal and intestinal alterations and affects renal physiology (Nobre et al, 2003;Moreno et al, 2003). Thus, it could be assumed that MCs affected the functions of the detoxification system of these organs.…”
Section: Discussionmentioning
confidence: 99%
“…MCs are also proved to promote renal and intestine alterations and affect renal physiology (Nobre et al, 2003;Moreno et al, 2003). Anemia caused by MC-induced kidney function impairment is suggested to be responsible for the abnormality of swimming behaviors .…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is associated with the pathophysiology of many cardiomyopathies, such as anthracycline-mediated cardiomyopathy (Singal et al, 1997;Xu et al, 2001) and alcoholic cardiomyopathy (Edes et al, 1986). Nowadays, accumulating evidences imply that MC-dependent damage is accompanied by oxidative stress in liver, kidney and intestinal mucosa in mammals (Botha et al, 2004;Ding et al, 1998Ding et al, , 2001Moreno et al, 2003Moreno et al, , 2005. Moreover, studies strongly indicate that mitochondria are the vulnerable target of MC.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacterial extracts can also enhance intracellular production of reactive oxygen species (ROS) (Ding et al, 1998). It is widely reported that MCs induce oxidative stress in many animals: mice, rat and aquatic organisms such as crab and fish (Moreno et al, 2003;Pinho et al, 2005;Prieto et al, 2006;Jayaraj et al, 2006).…”
Section: Introductionmentioning
confidence: 99%